Philosophy, psychoanalysis, and the A-rational mind - Brakel, Linda A. W. (International perspectives in philosophy and psychiatry., 2009)
Psychoanalytic theories have come in out of favour in the past hundred years. As a central theory behind recent empirically validated treatments such as mentalisation based therapy, there is a newfound interest in considering just what psychoanalysis can offer us in psychiatry and philosophy of mind. Philosophy, Psychoanalysis, and the A-Rational Mind is an interdisciplinary book with two aims. Firstly, to sharpen psychoanalytic concepts using philosophical tools and make psychoanalytic theory more viable to the academic community. Secondly, it looks to expand philosophy of mind so as to consider serious accounts of the unconscious and non-rational mental material predominant and ever-present in psychoanalytic data. The book explores some basic psychological phenomena- beliefs, desires, phantasies, wishes, and drives- examining a range of fascinating cases, and explaining their significance for both philosophers and psychoanalysts. The book revisits some of Freud's less famous cases (and one of his most famous) while exploring some lesser known phenomena such as akrasia (weakness of will). The book provides a powerful re-appraisal of psychoanalysis and the role it can play in helping us better understand human nature.